2013
DOI: 10.1097/qai.0b013e31827f1bdb
|View full text |Cite
|
Sign up to set email alerts
|

Neurovirological Correlation With HIV-Associated Neurocognitive Disorders and Encephalitis in a HAART-Era Cohort

Abstract: Objective Replicating HIV-1 in the brain is present in HIV encephalitis (HIVE) and microglial nodule encephalitis (MGNE) and is putatively linked with HIV-associated neurocognitive disorders (HAND). A clinico-neurovirological correlation was conducted to elucidate the relationship between brain viral load and clinical phenotype. Subjects and assays HIV gag/pol RNA and DNA copies were quantified with RT-PCR or PCR in 148 HAART-era brain specimens. Comparison to HAND, HIVE and MGNE and correlation with neurops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 41 publications
(56 reference statements)
6
100
1
3
Order By: Relevance
“…The current study concurs with this suggestion, since in more recent publications examining the neuropathology in treated HIV+ patients, the classic signs of inflammation damage such as multinucleated giant cells and HIV encephalitis were lacking. Those results suggested alternative causes for the progressive neurodegeneration in this patient group (Everall et al, 2009, Gelman et al, 2013) and exposure to viral protein is one of those suggested causes (Shin and Thayer, 2013, Silverstein et al, 2012, Yadav and Collman, 2009). The subcortical pattern of neuronal damage that we see in our animals is also reminiscent of HIV damage in the post ART era (Kumar et al, 2009, Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
“…The current study concurs with this suggestion, since in more recent publications examining the neuropathology in treated HIV+ patients, the classic signs of inflammation damage such as multinucleated giant cells and HIV encephalitis were lacking. Those results suggested alternative causes for the progressive neurodegeneration in this patient group (Everall et al, 2009, Gelman et al, 2013) and exposure to viral protein is one of those suggested causes (Shin and Thayer, 2013, Silverstein et al, 2012, Yadav and Collman, 2009). The subcortical pattern of neuronal damage that we see in our animals is also reminiscent of HIV damage in the post ART era (Kumar et al, 2009, Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
“…In turn, the control group showed a decrease in the number of hippocampal cells, and histopathologically glial nodules and vessel proliferation were detected. Glial nodules may be associated with an inflammatory process and responsible for provoking learning and memory impairment [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral neuroinvasion involves the recruitment of infected monocytes/macrophages and/or T cells to the central nervous system (CNS) from circulation, with activation and productive infection of resident microglia and a more restricted/latent infection of astrocytes (4)(5)(6)(7)(8)(9). HIV-1 infection of mononuclear phagocytes in the CNS has been suggested to be the critical driving force of HIV-induced encephalitis (HIVE), as well as HAND (10,11). Infected cells in the brain release neurotoxic viral and host inflammatory proteins that result in neuronal injury and death (6,12).…”
mentioning
confidence: 99%